Analisis Kinerja Rantai Pasok Produk Kedelai Menggunakan Metode Supply Chain Operation Reference - Fathoni, M Yoka; Prabowo, Dedy Agung; Wijayanto, Sena; Fernandez, Sandhy; Susanto, Ardi (Politeknik Harapan Bersama, 2022)
Indonesia is a country that has one of the advantages, namely as the largest agricultural country that has natural wealth, one of which is the agricultural sector. Soybean is one of the most widely grown crops in Indonesian agriculture and is included in the legumes group which has the highest vegetable protein content when compared to other types of beans such as red beans, green beans, and peanuts. The use of the SCOR method in this study is to measure good SCM performance, because SCOR divides supply chain processes into five 5 core processes, namely plan, source, make, deliver and return, where these processes have represented all supply chain activities. management from upstream to downstream in detail, so that it can define and categorize the measurement indicators needed in measuring Supply Chain Management performance. Based on the SCOR method, the results of the calculation of the final performance value of the soybean supply chain in the province of Central Java are 76.8 out of 100 which are in the